In pursuit of an HIV cure: from stem cell transplants to gene therapies - Clees, Jennifer; Basic, Maya; Cruz, Pedro E.; Ramirez, Servio H.; Andrews, Allison M. (Frontiers in Genome Editing, 2025)
Since 2009, seven people living with human immunodeficiency virus (PLHIV) have been declared cured of HIV after receiving allogeneic hematopoietic stem cell transplants (alloHSCTs) to treat hematologic malignancies. In this sense, cure signifies the absence of viral DNA/RNA and undetectable viral loads without the use of antiretroviral therapy (ART). Five of these transplants utilized mutated C-C motif chemokine receptor type 5 (CCR5Δ32/Δ32) stem cells. Much has been learned from these and past cases, and although effective, bone marrow transplants cannot be easily or safely translated to cure the millions of PLHIV across the globe. A successful eradicating cure includes both the prevention of HIV from entering new cells and the elimination of tissue reservoirs. Protecting hematopoietic stem and progenitor cells (HSPCs) from infection is a key consideration since there is evidence that HSPCs themselves, not only their descendants, are susceptible to infection. Gene therapy approaches have the potential to bring about an eradicating HIV cure that could be highly effective, broadly applicable, less expensive, and practical to implement. Current strategies are tackling this problem by removing the integrated proviral DNA from infected cells and/or eliminating the co-receptor(s) necessary for HIV viral entry into target cells. Both approaches hold promise, but they require overcoming key challenges (i.e., vector toxicity, transduction efficacy, elimination of reservoir cells, etc.). This review summarizes and examines the lessons learned about curing HIV through bone marrow transplants, the current gene therapy methodologies, pitfalls of eradication strategies as well as future directions of the field.